Educating Providers on Proactive Smoking Cessation Treatments in Primary Care - Gilbert, Paige; Dowd, Bree-Ann; Dabney, Beverly W.; Linton, Mary (Journal for nurse practitioners, 2025)
Smoking remains the leading cause of preventable death worldwide. Despite available treatments, quitting rates are low without proper support. In a primary care setting, proactive smoking cessation interventions were not routinely provided. A quality improvement project using quasi-experimental design focused on educating providers and actively engaging smoking patients. Post-intervention, there was a significant increase in the percentage of patients offered smoking cessation treatments (38.5% to 84.6%, P = .016). However, there was no significant change in treatment acceptance rates. Educating providers increased treatment offers. Further research is needed to understand barriers to treatment acceptance. •Cigarette smoking remains the leading cause of preventable death globally.•Providers received smoking cessation education at a primary care clinic.•Treatment offers rose from 38.5% to 84.6% post-intervention.•Further research is needed on factors affecting patient treatment acceptance rates.